1975
DOI: 10.1182/blood.v45.5.671.671
|View full text |Cite
|
Sign up to set email alerts
|

Direct effects of thyroid hormones on bone marrow erythroid cells of rats

Abstract: A stimulatory effect on bone marrow cellularity was observed in normal and nephrectomized rats continuously infused with T3 and T4. Results of bone marrow studies are expressed in absolute numbers of total nucleated erythroid cells per milligram of femoral marrow at the beginning and after 8 hr of continuous intravenous infusions. Administration of T3 and T4 to nephrectomized rats produced a marked and significant increase in total erythroid cells counted. After differential analyses of the nucleated erythroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 16 publications
1
16
1
Order By: Relevance
“…The baseline determinations of T3 serum levels were in the range reported by others in patients with similar degree of impairment of renal function [24] and the prescribed dose of T3 was sufficient to produce a suppressive effect on TSH. The doses of T3 used in rats by Malgor et a1 [22] are about 700 times higher, per kilogram of body weight than the doses received by our patients. It is therefore possible that larger doses might induce an erythropoietic effect in man.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The baseline determinations of T3 serum levels were in the range reported by others in patients with similar degree of impairment of renal function [24] and the prescribed dose of T3 was sufficient to produce a suppressive effect on TSH. The doses of T3 used in rats by Malgor et a1 [22] are about 700 times higher, per kilogram of body weight than the doses received by our patients. It is therefore possible that larger doses might induce an erythropoietic effect in man.…”
Section: Discussioncontrasting
confidence: 46%
“…The purpose of the study was to test clinically the direct erythropoietic effect of T3 shown experimentally by Malgor and associates [22] to occur in the absence of erythropoietin. The criteria for selection limited the number of patients available for study but provided a hemogeneous group in which the results could be more easily interpreted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both in vivo [7] and in vitro [8,9] studies have suggested that thyroid hormone has a direct effect upon erythropoiesis of adult animals. The in vitro studies with canine marrow cells showed that thyroid hormones increased erythroid colony formation, although erythropoietin was a requisite for colony growth.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms by which TH stimulate the haemopoietic stem cells remain unclear. It was found that the stimulatory effect of TH hormones may be conditioned by a direct influence of TH on cells (Malgor et al, 1975) manifested in facilitating DNA transcription leading to the synthesis of new proteins (Tata, 1963;Tata & Widnell, 1966). A hypothesis was framed (Oppenheimer & Surks, 1975) that the effect of TH on the cells is dependent on the number of 'nuclear binding sites ' (NBS) , 1973).…”
Section: The Haematocrit Number Of Erythrocytes and Leucocytes In Thmentioning
confidence: 99%